First description of Giardia duodenalis in buffalo calves (Bubalus bubalis) in southwest region of São Paulo State, Brazil - de Aquino, Monally Conceição Costa (Food Waterborne Parasitol, 2019)
We performed molecular characterization of Giardia duodenalis in buffalo calves from the Southwest region of São Paulo State, Brazil. A total of 183 fecal samples of Murrah breed buffaloes up to six months of age were collected. We examined these samples by the polymerase chain reaction (PCR) targeting the small-subunit ribosomal RNA gene and positive samples were characterized using additional PCR assays targeting a portion of the beta-giardin, the glutamate dehydrogenase and the triose-phosphate isomerase genes. Based on the SSU rRNA nPCR, the presence of G. duodenalis was confirmed in 12 (6.56%) of fecal samples, of these, five, four and three samples were positive for the tpi, bg and gdh genes, respectively. Assemblage identification by sequencing was successful in 6 of 12 samples and sequence analysis showed 100% genetic similarity with G. duodenalis assemblage E. This observation represents the first detection of G. duodenalis assemblage E in buffaloes calves in Brazil.